(untitled) (International Nexus Multidisciplinary Research Journal, 2026)
Conflict is a disagreement or clash between individuals or groups arising from differences in opinions, interests, values, or objectives, which may lead to tension, hostility, or disruption within organizational or institutional context. The study examined the effectiveness of the conflict management technique(s) employed and conflict resolution in Nnamdi Azikiwe University Teaching Hospital Nnewi, Anambra State Nigeria within the period, 2010-2023. Specifically, The study examined the effect of conflict management technique(s) in use in the hospital on the commitment of medical doctors to the accomplishment of assigned tasks in the teaching Hospital, Nnewi and determined whether conflict management technique(s) in use has effect on job satisfaction and turnover rate of medical doctors in Nnamdi Azikiwe University Teaching Hospital, Nnewi. The Thomas Kilmann Conflict Mode Instrument was adopted as the theoretical framework for the study. The survey research was adopted and data were generated from questionnaires and interviews. The population used for the study is nine hundred and fifty four (954), made up of all the medical doctors and other relevant stakeholders in Nnamdi Azikiwe University Teaching Hospital Nnewi (NAUTH). The sample size of 410 was determined using the Krejecie and Morgan sample size determination formula. Descriptive statistical tools were used to collate and analyze the data generated while inferential statistical tools were used to test the hypotheses. Findings revealed that there are specific conflict management techniques employed by the management of the hospital to address conflict situations in Nnamdi Azikiwe University Teaching Hospital Nnewi and that the techniques so employed are not very effective in resolving conflict situations in the hospital, that unresolved conflicts has implications on the quality of health-care delivery of medical doctors in Nnamdi Azikiwe University Teaching Hospital Nnewi, that the conflict management techniques in use in the hospital has an effect on the commitment of medical doctors to the accomplishment of assigned tasks in Nnamdi Azikiwe University Teaching Hospital, Nnewi and that conflict management techniques in use have an effect on job satisfaction and turnover rate of medical doctors in Nnamdi Azikiwe University Teaching Hospital, Nnewi. The study recommend that to address the negative implications of ineffective conflict management techniques and boost medical doctors’ confidence, management should overhaul existing conflict management techniques, soliciting feedback from staff to inform improvements for effective conflict resolution. To ensure continued commitment of medical doctors to assigned tasks, federal government should explore ways to build into the industrial relations systems Acts that will checkmate abuses to collective agreements and also foster a supportive work environment that promotes work-life balance, address burnout and establish clear, transparent and fair conflict resolution policies and procedures.